Evaluation of Galectin-3 as a Novel Diagnostic Biomarker in Patients with Heart Failure with Preserved Ejection Fraction - Kanukurti, Jyothirmayi; Mohammed, Noorjahan; Sreedevi, N. N.; Khan, Siraj Ahmed; Baba, K.S.S. Sai; Bhaskar, M. Vijaya; Satish, O. Sai; Naushad, Shaik Mohammad; Mohan, Iyyapu Krishna (Journal of Laboratory Physicians, 2020)
Background Heart failure is a complex cardiovascular disease with a variety of etiologies and heterogeneity. The N-terminal pro-B-type natriuretic peptide (NT-proBNP) value has limited usefulness in diagnosing heart failure with preserved ejection fraction (HFpEF).Aim The aim of the present study is to evaluate serum Galectin-3 as a diagnostic biomarker in patients with HFpEF and to compare Galectin-3 with NT-proBNP levels.Materials and Methods A cross-sectional case–control study including 63 cases of heart failure with ejection fraction ≥50% confirmed by echocardiography. NT-proBNP levels in serum were measured by electrochemiluminescence immunoassay and Galectin-3 levels in serum were measured by using an enzyme-linked-immunosorbent serologic assay kit.Results The median levels of serum Galectin-3 and NT-proBNP in patients were significantly higher than those of controls (26.59 vs. 5.27 and 927 vs. 49.3, p < 0.0001). A positive correlation was observed between serum levels of Galection-3 and NT-ProBNP (r: 0.21, p = 0.048). At cut-off values of 10.1 ng/mL and 160 pg/mL, serum Galectin-3 has 77.78% sensitivity, 95% specificity with an area under the curve (AUC) of 0.93, and serum NT-proBNP has 71.43% sensitivity, 100% specificity with an AUC of 0.87, respectively, for diagnosing HFpEF. The comparison of receiver operating characteristics curves showed that Galectin-3 has better AUC compared with NT-proBNP in diagnosing HFpEF. Serum Galectin-3 showed a positive correlation with NT-proBNP and lipid parameters.Conclusion Galectin-3 with higher sensitivity and AUC can be used as a valuable biomarker for the diagnosis of HFpEF. Simultaneous testing of both Galectin-3 and NT-proBNP can further improve the detection of patients with HFpEF.
Keywords: sensitivity; Galectin-3; Heart failure; NT-proBNP; preserved ejection fraction